Water Quality Credit Trading: General Principles - Tara Wade; Tatiana Borisova (EDIS, 2022)
Protection of the quality of Florida water resources is an important priority for the public and the government agencies (Figure 1). Pollution of surface water (e.g., lakes, rivers, and streams) can be linked to fish kills, changes in the color and aesthetic appeal of the resource, changes in the quality of habitat for aquatic plant and animal life (leading to changes in the plant and animal communities), and to human health issues. To address the pollution problems, a variety of programs is implemented at the federal, state, and local levels. Despite these programs, water quality problems persist. A recent FDEP water quality assessment report shows that the concentration of nitrogen in surface water is increasing in some Florida regions, and most assessed rivers, streams, canals, lakes, and estuaries were not meeting surface water quality standards (FDEP 2016). Although there have been gains in pollution reduction, reducing pollution and improving water quality is still a public policy objective in Florida. Costs to implement Florida's water policy objective will be borne by Florida citizens and businesses. Market-based programs, such as water quality credit trading, can provide environmental benefits at lower costs and more quickly than other policy instruments (Shortle 2013). In this document, we review the basic components of a water quality credit trading program and discuss opportunities and challenges associated with a water quality credit trading program design. Technical terms used in this publication are bolded, and a glossary is available at the end of the document.